The role of the different CD3γ domains in TCR expression and signaling - Garcillán, Beatriz; Megino, Rebeca F.; Herrero-Alonso, Marta; Guardo, Alberto C.; Perez-Flores, Veronica; Juraske, Claudia; Idstein, Vincent; Martin-Fernandez, Jose M.; Geisler, Carsten; Schamel, Wolfgang W. A.; Marin, Ana V.; Regueiro, Jose R. (Frontiers in Immunology, 2022)
The CD3 subunits of the T-cell antigen receptor (TCR) play a central role in regulation of surface TCR expression levels. Humans who lack CD3g (g-) show reduced surface TCR expression levels and abolished phorbol ester (PMA)-induced TCR down-regulation. The response to PMA is mediated by a double leucine motif in the intracellular (IC) domain of CD3g. However, the molecular cause of the reduced TCR surface expression in g- lymphocytes is still not known. We used retroviral vectors carrying wild type CD3g or CD3d or the following chimeras (EC-extracellular, TM-transmembrane and IC): dECgTMgIC (dgg for short), ggd, gdd and gg-. Expression of ggg, ggd, gdd or gg- in the g- T cell line JGN, which lacks surface TCR, demonstrated that cell surface TCR levels in JGN were dependent on the EC domain of CD3g and could not be replaced by the one of CD3d. In JGN and primary g- patient T cells, the tested chimeras confirmed that the response to PMA maps to the IC domain of CD3g. Since protein homology explains these results better than domain structure, we conclude that CD3g contributes conformational cues that improve surface TCR expression, likely at the assembly or membrane transport steps. In JGN cells all chimeric TCRs were signalling competent. However, an IC domain at CD3g was required for TCR-induced IL-2 and TNF-a production and CD69 expression, indicating that a TCR without a CD3g IC domain has altered signalling capabilities.